PENGEMBANGAN MODEL KONTEKSTUAL PENDIDIKAN BOLA BASKET BERBASIS CHARACTER BUILDING (PEMBANGUNAN KARAKTER) - Mulyono, Aris (Universitas Negeri Semarang, 2013)
Important issues in physical education is how to include the development of good values or character well into the process of teaching physical education. Basketball sports also have a certain social character, such as the promi- nence of individualistic traits but in practice requires teamwork. This study is a research development (developmental research) to improve the learning process by strategizing and education model contextual teaching and learning (CTL) in basketball as a basis for the development of character, especially honesty, discipline, responsibility and cooperation within and outside the basketball court at school-age children basic education (elementary-Junior school). Method of approach used in this study is the research and development (research and development). With a sample SD Karangturi and Tri Tunggal, because elementary school has the best basketball performance event in Semarang state last 5 (five) years Based on the results of the assessment rubric completed by teacher assessment Penjasorkes obtained: (1) for the courage aspect of 100 students, which includes both categories totaled 77 students or approximately 77%, medium category were 18 students or approximately 18%, and a total lack of class 5 students or approximately 5%. (2) for the discipline aspect of 100 students, which includes both categories totaled 77 students, or about 77%, the categories are numbered 21 students, or about 21%, and less than 2 categories of students, or about 2%. (3) for the cooperative aspects of 100 students, which includes both categories are 71 students or approximately 71%, the categories are numbered 28 students, or about 28%, and category 1 students or less amounted to approximately 1%. (4) for the honesty aspect of 100 students, which includes both categories totaled 80 students, or about 80%, the categories are numbered 17 students, or about 17%, and category 3 students or less amounted to approximately 3%. (5) the responsibility for aspects of 100 students, which includes both categories are 71 students or approximately 71%, of the 27 categories were students or approximately 27%, and less than 2 categories of students or approximately 1%. Conclusions from this research is the development of product use contextual model of education based on character building basketball (character development) for students to assist students in improving the character through basketball proved to be more than 71% of students who had positive feedback about some aspects of the affective anah include: courage, discipline, cooperation, honesty, and responsibility.